The Effect of Provincial Minimum Wage, Open Unemployment Rate, and Average Years of Schooling on Labor Force Participation Rate in East Java Province - Amelya Romawati; Ririt Iriani Sri Setiawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research is motivated by human resources as a factor in economic development. Population productivity is measured through the labor force participation rate (LFPR). East Java Province is ranked second in LFPR in Java Island along with the fourth rank for the level of completion of high school/vocational high school education among provinces in Java Island. This study highlights education which is one of the factors in the LFPR benchmark in addition to minimum wages and open unemployment rates. This analysis was conducted using the classical assumption test, multiple linear regression analysis, t-test and F-test. The results of the analysis produced a provincial minimum wage variable with a negative and significant effect, the open unemployment rate with a negative and insignificant effect, while the average length of schooling had a positive and significant effect.